2017
DOI: 10.5507/bp.2017.031
|View full text |Cite
|
Sign up to set email alerts
|

Left hippocampus sparing whole brain radiotherapy (WBRT): A planning study

Abstract: Aims. Unilateral sparing of the dominant (left) hippocampus during whole brain radiotherapy (WBRT) could mitigate cognitive decline, especially verbal memory, similar to the widely investigated bilateral hippocampus avoidance (HA-WBRT). The aim of this planning study is dosimetrical comparison of HA-WBRT with only left hippocampus sparing (LHA-WBRT) plans. Methods. HA-WBRT plans for 10 patients were prepared in accordance with RTOG 0933 trial and served as baseline for comparisons with several LHA-WBRT plans p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It has been shown that unilateral hippocampal avoidance during WBRT can also mitigate cognitive decline, formation of memory, verbal memory, similar to bilateral HA-WBRT [ 33 36 ]. Furthermore, meta-analysis of 33 studies, which evaluated memory before and after resection of left or right anterior temporal lobe for temporal lobe epilepsy has observed difference in verbal memory function after resection from the left or right temporal lobe [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that unilateral hippocampal avoidance during WBRT can also mitigate cognitive decline, formation of memory, verbal memory, similar to bilateral HA-WBRT [ 33 36 ]. Furthermore, meta-analysis of 33 studies, which evaluated memory before and after resection of left or right anterior temporal lobe for temporal lobe epilepsy has observed difference in verbal memory function after resection from the left or right temporal lobe [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the hypothesized noninferiority of unilateral sparing, there would be a possible advantage of about 50% reduction in the risk of subsequent recurrence within spared regions based on our current observation of no significant difference in the laterality of BM seeding. Moreover, unilateral hippocampal avoiding leads to dosimetrically increased sparing of preserved hippocampus [21].…”
Section: Discussionmentioning
confidence: 99%
“…This novel approach of unilateral hippocampus sparing WBRT would be associated with reduced concern regarding subtherapeutic dose in spared regions and with the possibility of improved sparing of single hippocampus. In our pilot dosimetric study, left unilateral sparing yielded lower doses in spared hippocampus with a more homogenous irradiation of the remaining brain [21]. To justify clinical testing of this radiotherapy technique, it would be useful to evaluate whether there is some difference in the incidence of BM within left versus right hippocampus; however, no prior study has assessed the laterality of hippocampal BM seeding.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and automatic hippocampus segmentation from magnetic resonance (MR) brain images is important in several neuroimaging studies of brain disorders, such as brain cancer, epilepsy, and Alzheimer’s disease (AD) 13 . To achieve fully automated hippocampus segmentation, atlas-based methods have been proposed for hippocampus segmentation 4 .…”
Section: Introductionmentioning
confidence: 99%